Constraining invader dominance: Effects of repeated herbicidal management and environmental factors on curlyleaf pondweed dynamics in 50 Minnesota lakes. (3rd January 2020) - Verhoeven, Michael R.; Larkin, Daniel J.; Newman, Raymond M.
Abstract: Curlyleaf pondweed ( Potamogeton crispus ) is one of the most widespread and widely managed aquatic invasive plants in North America. Despite decades of management, the efficacy of long‐term management strategies and the effects of environmental drivers on curlyleaf pondweed populations remain uncertain. To evaluate the effects of management and environmental factors on within‐lake distribution and local density of curlyleaf pondweed, we collated monitoring data from point–intercept surveys collected by a variety of lake managers across Minnesota, U.S.A. Using this dataset, comprising 177 lake‐years of plant data, we examined the influence of herbicide treatment, water clarity, snow depth, and ice cover duration on curlyleaf pondweed distribution and density between 2006 and 2015. We evaluated the effects of herbicides on curlyleaf pondweed at three time points relative to treatment: within year, carryover effects the following year, and cumulative effects over multiple years of treatment. All three temporal measures were associated with significant reductions of curlyleaf pondweed. Additionally, herbicidal management reduced both the density and distribution of curlyleaf pondweed. Given that herbicide management led to reductions that carried over into future years, managers may be able to design multi‐year treatments to reduce total management effort over time. We also found strong effects of environmental conditions on curlyleaf pondweed. Elevated lake productivity and decreased winter snow cover were associated with increased springtime distributions of curlyleaf pondweed, whereas duration of winter ice cover had no influence. The influence of productivity suggests that reductions of this invasive species may be an ancillary benefit of water‐quality improvements that lower lakes' trophic status. Our results also show that decreased winter snow cover, as predicted under climate change, could exacerbate problematic growth of curlyleaf pondweed. Harnessing monitoring data from multiple projects, as this study does, allows for robust inference about environmental and management constraints on macrophytes. Because of environmental and management variability, we suggest that treatment regimens follow an adaptive management cycle, with outcomes of management monitored and evaluated, and strategies updated accordingly. It is also vital to continue monitoring both managed and unmanaged lakes to enable stronger inferences about treatment effectiveness.